Pembelajaran Tahfidzul Qur'an Di Sekolah Dasar Islam Terpadu(SDIT) Mutiara Insan Dan Sekolah Dasar Islam Terpadu (SDIT) Fatahillah Sukoharjo Tahun Pelajaran 2016/ 2017 - Indriyani, Indriyani, Dr. Syamsul Hidayat, M.Ag, Dr. Muthoifin, M.Ag (2016)
Elementary School Islam is a form of education unit basic education programs six years based on the national curriculum is enriched by the system of Islamic education through the integration between religious education and general education, between school, parents and the community to maximize cognitive, effective and psychomotor with expectations learners become intelligent, insightful, creative and be positive. The problem in this research that there still exists some Islamic educational institutions were not capable to keep learning tahfidz/ memorize the Qur'an effectively because due to the system used is not optimal. While in SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo for effective lerarning outcomes tahfidzul Qur'an used 'ummy method to SDIT Mutiara Insan and variety of methods to SDIT Fatahillah Sukoharjo. The purpose of this study to investigate the implementatition of learning tahfidzul Qur'an in SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo and supporting factors and inhibit the progress of the learning. This study uses qualitative descriptive method in use in SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo for 3 months. It is July 2016 to September 2016. The subjects the students and teachers at SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo. While theinformant was principal at SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo. Data collected by observation, interview and documentation. The validity of the data obtained througt the uses of triangulation by uses the triangulation techniques. Data were analyzed with data reduction, data presentation and conclution. The results showed that the implementation of learning tahfidzul Qur'an in SDIT Mutiara Insan and SDIT Fatahillah Sukoharjo as follows: learning thafidzul Qur'an in SDIT Mutiara Insan: the material provided to students is the Qur'anic juz 29 to juz 30, makharijul huruf and the tajwid. The method used in memorizing the Qur'an is a wahdah method, sima'I method, the combained method and the method in which the core jama'I of memorizing the Qur'an is by constanly repeated with patience and persistence, while supporting programs such as evaluation, monitoring tahfidz book and tasks. There are two system evaluation learning there are written and orally, when the UTS (Ulangan Tengah Semester) and UAS/UKK (Ulangan Akhir Semester/ Ulangan Kenaikan Kelas). Supporting factors tahfidzul Qur'an learning in in SDIT Mutiara Insan is: children actively memorize; always read repeatedly with a friend is to be made of the group; repeatedly by parents at home. Inhibiting factors in memorizing the Qur'an, there are: children are not actively memorize; do not want to read repeat over and over again with a friend is to be made of the group or silent; do not repeatedly by parents at home. The results showed that the implementation of learning tahfidzul Qur'an in SDIT Fatahillah Sukoharjo is like this material SDIT Fatahillah students then getting material tahfidz, students were also given the tajwid material. Material provided is the Qur'an juz 29 to juz 30. The learning method tahfidzul Qur'an in SDIT Fatahillah Sukoharjo using different methods. There are wahdahmethod, sima'i method, jama'imethod. Evaluation system, to determine the successess and shortcomings in the evaluation of an activity. The evaluation system in SDIT Fatahillah Sukoharjo is done every UTS, UAS or UKK. Materials provided in the form of rote memorization required and additional. Memorizing tahfidz shall be determined by the teacher of each class. And rote memorization choice that has been achieved by each students. Supporting factors tahfidzul Qur'an learning in Fatahillah Sukoharjo, there are: support of parents; intelligance; ability to read the Qur'an. Inhibiting factorsin memorizing the Qur'an, there are: lack of parental support in term of memorizing the Qur'an; the intelligance of children; do not fluent in reading the Qur'an making it dificult to the child while memorizing properly.